Pengaruh Penerapan Green Accounting, Environmental Performance dan Manajemen Laba terhadap Sustainable Growth - Nizar, Muhamad; Mulyani, Susi Dwi (SAFE-Network, 2023)
This study aims to examine the influence of green accounting, environmental performance, and earnings management on sustainable growth, with financial leverage as a control variable. The population of this study consists of companies listed on the Indonesia Stock Exchange (BEI) until December 31, 2021, with the addition of sample criteria including companies that have received environmental performance assessments from the Ministry of Environment and Forestry of the Republic of Indonesia. The data collected from the sample covers the period from 2017 to 2021. Data were collected from 91 different companies using purposive sampling technique. This study employed the Generalized Least Square (GLS) method through multiple linear regression with unbalanced panel data. Based on the analysis results, it can be concluded that green accounting has a significant positive effect on sustainable growth, environmental performance does not have an effect on sustainable growth, and earnings management does not have an effect on sustainable growth.